2019
DOI: 10.1002/pros.23904
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of certain transient receptor potential and Orai channels in prostate cancer is associated with decreased risk of systemic recurrence after radical prostatectomy

Abstract: Background: Several studies had suggested the potential role of calcium signaling in prostate cancer (PCa) prognosis and agressiveness. We aimed to investigate selected proteins contributing to calcium (Ca2+) signaling, (Orai, stromal interaction molecule (STIM), and transient receptor potential (TRP) channels) and involved in cancer hallmarks, as independent predictors of systemic recurrence after radical prostatectomy (RP). Methods: A case‐control study including 112 patients with clinically localized PCa tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…In addition, our findings show that the high expression of TRPC1 correlated with low overall survival in PDAC patients. However, the dysregulated expression of TRPC1 will remain controversial and seems to be cell type-specific, as the upregulation of TRPC1 appears to have a protective role in prostate [ 51 , 52 ] and some breast cancer patients [ 33 ]. Consistent with the increased TRPC1 mRNA expression, TRPC1 protein expression also significantly increased in human PDAC samples, where TRPC1 localizes to the plasma membrane, compared to adjacent non-tumor tissue, where it localizes in the cytoplasmic compartments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our findings show that the high expression of TRPC1 correlated with low overall survival in PDAC patients. However, the dysregulated expression of TRPC1 will remain controversial and seems to be cell type-specific, as the upregulation of TRPC1 appears to have a protective role in prostate [ 51 , 52 ] and some breast cancer patients [ 33 ]. Consistent with the increased TRPC1 mRNA expression, TRPC1 protein expression also significantly increased in human PDAC samples, where TRPC1 localizes to the plasma membrane, compared to adjacent non-tumor tissue, where it localizes in the cytoplasmic compartments.…”
Section: Discussionmentioning
confidence: 99%
“…STIM1-Orai1-TRPC1-mediated Ca 2+ entry is also required for platelet aggregation [72], insulin release [73], adipocyte differentiation and adiponectin secretion [74], among other functions. Moreover, STIM1-Orai1-TRPC1-dependent Ca 2+ currents have been associated to the Ca 2+ mobilization responsible for the development of distinct cancer hallmarks in different cancer cell types, including prostate cancer cells [75] and colon cancer cells [76,77], while STIM1-Orai1-TRPC1-TRPC4-mediated Ca 2+ currents are involved in the Ca 2+ remodelling involved in hypertrophic cardiomyopathy in rat ventricular myocytes [78]. A more recent study has reported that in anterior pituitary (AP) cells from Orai1-lacking mice TG-induced SOCE as well as Ca 2+ entry evoked by TRH and LHRH were impaired, by contrast, SOCE was unaffected in AP cells from mice lacking expression of all seven TRPC channels, although spontaneous intracellular Ca 2+ -oscillations associated to electrical activity as well as Ca 2+ responses to TRH and GHRH were significantly reduced in the absence of TRPC channels, thus suggesting that SOCE might function independently of TRPC channels and that Orai1 and TRPC channels, such as TRPC1, might play different functional roles [79].…”
Section: Trpc Channels In the Stim1-orai1 Scenariomentioning
confidence: 99%
“…Additionally, Zhang demonstrated that both the G protein-coupled receptor (GPCR) Gα q -subunit and PIP 2 were able to inhibit TRPM8 channels, and the TRPM8-Gα q binding impaired Gα q coupling and signaling to PLCβ-PIP 2 [60]. In this way, multivariate analysis showed that overexpression of TRPM8, and STIM2 is associated with a lower risk of systemic recurrence after radical prostatectomy [61]. Taken together, these studies suggest that Gα q -subunit and PLCβ-PIP 2 generating IP 3 could be a novel insight to further understand the structure-function relationships of TRPM8 and SOCE.…”
Section: Soce and Trpm8 Channels: An Ability To Regulate Different Pa...mentioning
confidence: 99%